Sex differences of post-Covid patients undergoing outpatient pulmonary rehabilitation - Alexander Kautzky; Stephan Nopp; Dietlinde Gattinger; Milos Petrovic; Martin Antlinger; Dustin Schomacker; Alexandra Kautzky-Willer; Ralf Harun Zwick (Biology of Sex Differences, 2024)
Abstract Background Following years of pandemic severe acute respiratory syndrome coronavirus 2 infections labelled Covid-19, long lasting impairment summarized as post-Covid syndrome (PCS) challenges worldwide healthcare. Patients benefit from rehabilitation programs, but sex specific aspects of improvement remain little understood. The aim of the study was to assess whether women and men differ in response to outpatient pulmonary rehabilitation for PCS. Methods 263 (54.4% female) patients partaking in outpatient pulmonary rehabilitation (OPR) due to PCS between March 2020 and July 2022 were included in a prospective observational cohort study. Outcomes were assessed at baseline and before discharge from OPR and included six-minute walking distance (6MWD), 1-second forced expiratory volume (FEV1), diffusion capacity for carbon monoxide, maximal inspiratory pressure (MIP), dyspnea (medical research council scale), and post-Covid functional status scale (PCFS). Sexspecific changes in outcomes following OPR were assessed by linear mixed model and presented as mean differences (MD) with 95% confidence intervals. Linear regression was applied to test whether 6MWD correlates with PCFS and the minimal clinically important difference (MCID) in 6MWD regarding an improvement of at least one point in PCFS was computed with logistic regression. Results Significant improvement throughout OPR was observed for all outcomes (all p < 0.0001). Despite less severe Covid-19 infections, PCFS scores remained higher in females after OPR (p = 0.004) and only 19.4% of women compared to 38.5% of men achieved remission of functional impairment. At baseline as well as after OPR, females showed higher symptom load compared to men in dyspnea (p = 0.0027) and scored lower in FEV1 (p = 0.009) and MIP (p = 0.0006) assessment. Performance in 6MWD was comparable between men and women. An increase of 35 m in 6MWD was computed as minimal clinically important difference to improve functional impairment. Conclusion Both subjective symptoms such as fatigue and dyspnea and objective impairment in performance in pulmonary function were more frequently observed among women. Despite improvement throughout OPR in both women and men, the sex-gap in symptom load could not be closed as women less often achieved remission from functional impairment due to PCS. Intensified treatment of these symptoms should be considered in women undergoing rehabilitation for PCS.